Preparation and characterization of Fe₃O₄/montmorillonite and Fe₃O₄/talc nanocomposites for removal of heavy metals - Kalantari, Katayoon (2015)
Toxic metal contamination in water systems is a serious problem threating environment. Many researches have been done to develop effective ways for the heavy metals removal. Traditionally methods used for removal have some disadvantages, such as low efficiency and high cost. Adsorption is one of the techniques use in this area due to its effectiveness and easy operation. In this work, Fe3O4/montmorillonite and Fe3O4/talc nanocomposites as nanoadsorbent were prepared by co-precipitation method in different percentages. The suitability of the magnetic nanocomposites for the adsorption of Cu2+, Ni2+ and Pb2+ ions and its efficiency were investigated. The Response Surface Methodology was used for designing the experiment sets. The analysis of variance for Cu2+, Ni2+ and Pb2+ removal was used to estimate the response of initial concentration of heavy metal ion (mg/L), removal time (s) and dosage of adsorbent (g). Transmission electron microscopy showed that the average nanoparticles size were between 8.24 to 12.88 and 6.62 to 8.13 nm for Fe3O4/montmorillonite and Fe3O4/talc nanocomposites, respectively. Scanning electron microscopy showed that the nanoparticles were highly uniform in size and spherical shape. X-ray diffraction and Energy-dispersive X-ray, confirmed that magnetic nanoparticles were prepared. Vibrating sample magnetometer reveals the nanoparticles were superparamagnetic. The Fe3O4/montmorillonite nanocomposite showed a better capability for adsorption of heavy metals from aqueous solution. The best interpretation for the equilibrium data was given by Langmuir isotherm and the kinetic data showed that the adsorption process followed the pseudo-second order kinetic model for both adsorbents. According to RSM results, for Fe3O4/montmorillonite nanocomposite, removal efficiency were 89.72%,94.89%, and 76.15% while the removal time was 120s, Fe3O4/montmorillonite nanocomposite amount were 0.06, 0.08 and 0.08 g and initial heavy metal concentrations were 510.16 for Cu2+, 182.94 for Ni2+ and 111.90 mg/L for Pb2+. Moreover for Fe3O4/talc nanocomposite, removal efficiency were 72.15%, 50.23%, and 91.35% while the removal time was 120s, Fe3O4/talc nanocomposite amount was 0.12 g and initial heavy metal concentrations were 100 for Cu2+, 92 for Ni2+ and 270 mg/L for Pb2+ ions. As a results two unique nano adsorbents made of montmorillonite and talc as a natural substrate and loaded magnetic nano particles were used to rapid remove of Cu2+, Ni2+ and Pb2+ ions from aqueous solution. The adsorbents can easily separate by an external magnetic field.